The Role of Parental Literacy in Shaping Student Character at MIN 3 Sumenep - Sofiyatinnisa Riskiyah; Ihwan Amalih (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to describe the role of parental literacy in shaping students’ character at MIN 3 Sumenep and to identify the obstacles faced in its implementation. This research employed a descriptive qualitative approach. The research subjects consisted of parents, teachers, and school stakeholders. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The findings showed that parental literacy was carried out through role modeling, learning assistance, motivation, reading habituation, and the inculcation of religious values within the family environment. These roles contributed to shaping students’ discipline, responsibility, religiosity, honesty, and social care. The obstacles encountered included parents’ limited time, diverse educational backgrounds, family economic conditions, and the low awareness of some parents regarding the importance of literacy. This study confirms that strengthening family literacy culture and synergy between schools and parents are highly necessary to support optimal student character development.